2009
DOI: 10.1080/01442870902899848
|View full text |Cite
|
Sign up to set email alerts
|

Has social care performance in England improved? An analysis of performance ratings across social services organisations

Abstract: Performance measurement in the English public sector has been implemented in a top-down manner. The mechanics of this regime (centralised targets, public reporting of performance data and the use of rewards and penalties) are driven by central government and are intended to hold agencies to account for their performance and regulate their behaviour. This paper examines whether the operation of such a regime has resulted in the improved performance of social care organisations. Comparable data from Northern Ire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Third, controlling gaming—the deliberate manipulation of behavior to secure strategic advantage in evaluation (Smith, )—is an endless and uphill battle. A number of studies show that many performance measurement systems instigate unintended behavioral change such as gaming (de Brujin, ; Hood, ; Courty and Marschke, ; Clarkson et al ., ; Knutsson et al ., ). Gaming emerges even though different countries adopt different performance measurement systems that prioritize very different types of measures.…”
Section: Challengesmentioning
confidence: 98%
See 1 more Smart Citation
“…Third, controlling gaming—the deliberate manipulation of behavior to secure strategic advantage in evaluation (Smith, )—is an endless and uphill battle. A number of studies show that many performance measurement systems instigate unintended behavioral change such as gaming (de Brujin, ; Hood, ; Courty and Marschke, ; Clarkson et al ., ; Knutsson et al ., ). Gaming emerges even though different countries adopt different performance measurement systems that prioritize very different types of measures.…”
Section: Challengesmentioning
confidence: 98%
“…A case in point is the study of Clarkson et al . (), which examines whether a UK performance measurement system in the area of healthcare resulted in improved performance. Overall, they found a marked tendency for summary measures of performance—“star” ratings, to use the system's terminology—to have improved over time.…”
Section: Reform Outcomesmentioning
confidence: 99%
“…Schmid (2002) analysed the relationships between organizational properties and organizational effectiveness in, amongst others, home care organizations, and discovered that centralization of authority, formalization, workers' autonomy, coordination, control, empowerment and training had the most influence on organizational effectiveness. Clarkson et al (2009) evaluated the effects of performance measurement systems (comprising centralized targets, public reporting of data, and the use of rewards and penalties) that had been implemented in a top-down manner in the English social care sector, and concluded that these systems had helped social care organizations to improve their performance over time. Malley and Fernández (2010) discussed developments of theoretical and practical frameworks used for assessing quality in social care and for understanding the impact of services on the well-being of patients, using the "production of welfare" framework (Davies and Knapp, 1981;Knapp, 1984).…”
Section: Hpo Frameworkmentioning
confidence: 99%
“…The social care and rehabilitation sector Social care and rehabilitation organizations are public organizations working under a government framework of the law on social provision (Costa and Anderson, 2011). Social care is administered through local authorities, and in essence is a locally delivered service operating to centrally determined policy goals (Clarkson et al, 2009). The main goal of social care and rehabilitation is to maintain and enhance the individual well-being of people, by supplying services that try to achieve and sustain the optimum state of health of the recipients of these services (Schmid, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it was not possible to determine that performance improvement on a mass scale happened in the municipal intelligence regime in Quebec (Charbonneau, 2011, p. 548). The numerous comparative studies on the target regime in England, the rankings regime in Scotland and the intelligence regime in Wales are that performance improved on a mass scale in England (Clarkson et al, 2008;Andrews and Martin, 2010). With the insight that was not available to public managers putting together these performance regimes in the beginning of the 2000s, we offer a proposition.…”
Section: Discussionmentioning
confidence: 96%